Strategi Guru Pendidikan Agama Islam dalam Meningkatkan Akhlak Pada Siswa-Siswi MTsN 3 Banyuwangi - Aminin, Arif; Syahid, Mar; Fitria, Mulajimatul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) STIB Banyuwangi, 2023)
The results of this research show that there are several strategies that PAI teachers can use to improve students' morals, including motivation strategies, namely by using video based learning, through advice or providing insight, and through examples from the stories of the prophets and apostles, in implementation strategies. namely by designing learning objectives according to the curriculum, through habits, and through examples from teachers, and evaluation strategies, namely by game based learning evaluation methods, by involving the role of parents, and by portfolio-based evaluation or by interviews or interview with one of the students so you can find out what progress the student has made. Very positive results were obtained from these programs, namely that students' morals or morals improved, so that students became more polite. This is in accordance with the results of interviews conducted with students. They always pray before class starts, pay attention to the teacher during class, picket, throw rubbish in their place, be kind to their peers, respect teachers both at school and outside school by saying hello and kissing hands, and always set an example of good behavior and not bad.